2019
DOI: 10.1111/bcp.13960
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic model and Bayesian estimator for 2 tacrolimus formulations in adult liver transplant patients

Abstract: Aims: Tacrolimus is a narrow therapeutic range drug that requires fine dose adjustment, for which pharmacokinetic (PK) models have been amply proposed in renal, but not in liver, transplant recipients. This study aimed to build population PK models and Bayesian estimators (BEs) in adult de novo liver transplant patients receiving either the immediate-release (Prograf, twice daily, TD) or prolonged-release (Advagraf, once daily, OD) forms to help PK-guided dose individualization.Methods: In total, 160 tacrolimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…(0, 0.33, 0.66, 1, 2, 3, 4, 6, 8, 12, 13, 15, and 24 hours postdosing) collected at 7 days and 3 months postrenal transplantation. In liver transplant recipients, 14 our database included 68 PK profiles of 9 samples for TAC b.i.d. (0, 0.5, 1, 2, 3, 4, 6, 8, and 12 hours postdosing) and 91 PK profiles of 17 samples for TAC q.d.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(0, 0.33, 0.66, 1, 2, 3, 4, 6, 8, 12, 13, 15, and 24 hours postdosing) collected at 7 days and 3 months postrenal transplantation. In liver transplant recipients, 14 our database included 68 PK profiles of 9 samples for TAC b.i.d. (0, 0.5, 1, 2, 3, 4, 6, 8, and 12 hours postdosing) and 91 PK profiles of 17 samples for TAC q.d.…”
Section: Methodsmentioning
confidence: 99%
“…For that, two datasets of TAC b.i.d. in renal transplant recipients, 7,11 one in liver transplant recipients, 14 and one in heart transplant recipients, 15,16 as well as a dataset of TAC q.d. in renal transplant recipients 7 and another one in liver transplant recipients 14 were used.…”
Section: Plan Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that using a population pharmacokinetics-based Bayesian model (a statistical pharmacology model using large volumes of clinical data) with sparse sampling improves target achievement over traditional therapeutic drug monitoring in adults, and has been applied to pediatrics clinically. 13,14 The incorporation of pharmacogenetics factors, such as CYP3A5*3 and CYP3A4*22 genotypes, has further reduced variability and improves prediction of drug exposure. 9 A randomized clinical trial in pediatrics showed that CYP3A5 genotypeguided dosing based on age resulted in earlier attainment of target concentrations.…”
Section: Researchmentioning
confidence: 99%
“…Fortunately, population pharmacokinetic models and Monte Carlo simulation can be used to assist in optimizing the initial dosage (15,16). Since the initial clinical use of tacrolimus, several population pharmacokinetics models based on patients receiving a liver transplant have been built (17)(18)(19)(20)(21)(22). However, the precise treatment of tacrolimus and a model for the recommended initial dose in Chinese patients undergoing pediatric liver transplants has not been determined.…”
Section: Introductionmentioning
confidence: 99%